Preventing mycelial spread of Heterobasidion annosum in young Scots pine stands using fungal and viral biocontrol agents - Piri, Tuula; Vainio, Eeva J.; Hantula, Jarkko (Elsevier BV, 2023)
Heterobasidion annosum is one of the most important causal agents of root rot of pines in Europe. The timing of cuttings to wintertime or stump treatment by control agents in summertime are used to prevent the spread of the fungus to new forest sites via aerial spores. However, there are no efficient control treatments for an already established infection except for changing the tree species to a resistant one, which often is not possible. In this study, we tested whether treating stumps around Heterobasidion disease centres by the biocontrol fungus Phlebiopsis gigantea could reduce the spread of the pathogen. In addition, we tested whether the infection of H. annosum by a debilitating mycovirus, HetPV13-an1, would affect the control efficacy. The results showed that the enlargement of disease centres was reduced by P. gigantea, and that this biocontrol effect was enhanced by the virus application. Furthermore, the results showed that the growth rate of P. gigantea varies not only between root systems, but also among different roots of a single stump.
Keywords: Pinus sylvestris; Root rot; Stump treatment; Phlebiopsis gigantea; Mycovirus